1994
DOI: 10.1002/ijc.2910580515
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing effect ofO6-alkylguanine derivatives on chloroethylnitrosourea cytotoxicity toward tumor cells

Abstract: O6-Alkylguanine derivatives are well known as chemical modulators of the DNA repair enzyme O6-methylguanine-DNA methyltransferase (MGMT). Depletion of the enzyme by these derivatives leads to increase sensitivity of tumor cells to chloroethylnitrosoureas. We tested the effect of O6-methylguanine, O6-benzylguanine, O6-(p-methylbenzyl)guanine, O6-(p-chlorobenzyl)guanine, O6-(p-methoxybenzyl)guanine, O6-methylhypoxanthine and O6-benzylhypoxanthine on the sensitivity of tumor cell lines to 1-(4-amino-2-methyl-5-py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
1
12
1
Order By: Relevance
“…These findings are in agreement with previous immunohistochemistry studies (Ma et al, 2002). Clinical studies demonstrated that the MerϪ phenotype is often associated to a more positive outcome in chemotherapy based on alkylating agents, and several attempts are currently being made to inhibit chemoresistance using MGMT suicide substrates such as O 6 -benzylguanine or O 6 -(4-bromothenyl)guanine (Dolan et al, 1991;Mineura et al, 1994;Middleton et al, 2000b).…”
supporting
confidence: 91%
“…These findings are in agreement with previous immunohistochemistry studies (Ma et al, 2002). Clinical studies demonstrated that the MerϪ phenotype is often associated to a more positive outcome in chemotherapy based on alkylating agents, and several attempts are currently being made to inhibit chemoresistance using MGMT suicide substrates such as O 6 -benzylguanine or O 6 -(4-bromothenyl)guanine (Dolan et al, 1991;Mineura et al, 1994;Middleton et al, 2000b).…”
supporting
confidence: 91%
“…Three test compounds, 6-OHDA, MPP + and ACNU, that induce cytotoxicity in nerve cells were chosen and the protective effect of AGE (2 and 4 mg/ml) on cell death induced by these compounds was examined. 6-OHDA is a potent neurotoxin and induces cell death associated with ROS generation [20], whereas MPP + is an inducer of Parkinsonism and inhibitor of mitochondrial respiration chain [34] and ACNU is an alkylating anticancer drug used for the therapy of brain cancer [35]. The cytotoxicity of each compound in SH-SY5Y cells was examined and the dose-response curve of each compound was obtained.…”
Section: Concomitant Treatment Of Age Suppressed the Cell Death Inducmentioning
confidence: 99%
“…It is an intracelluIar dynamic model that describes a process of formation of DNA adducts when there is a capacity for removal of those adducts from the DNA by a repair enzyme. Many compounds and metabolities that bind 89 DNA also readily bind existing proteins; some classes of toxins and DNA adducts may inactivate the repair enzyme and subvert the repair process competitively (Chae et al, I994;Lijinsky et al, 1994;Mineura et al, 1994). This particular model illustrates the possible saturation of repair enzyme capacity by the toxin dosage and shows that bistable behavior can sometimes occur, inducing abrupt shifts between two possible steady-state equilibria.…”
mentioning
confidence: 98%